Music Pa'baeng: The Rainmaking Ritual of the Pariopo Tribe in Bantal Village, Situbondo Regency, East Java - Baidhowi, Ahmad (International Journal of Culture and Art Studies, 2021)
Pa'beng music is accompaniment music in Hodo ritual known as rain request ritual in Pariopo Tribe. Rituals that still run every year for the survival of ancestors since hundreds of years ago. The ritual is carried out at the peak of the drought arrives hoping that the rains fall so that the resulting harvest is abundant. Despite its development, this ritual changes and develops in line with the changing times. Nowadays, Pa'beng music develops and began to be known by the public with entertainment music without eliminating its authenticity. The art community of Bantal Village elevates Pa'beng music into entertainment music so that Pa'beng music can be known by the public and maintained its sustainability. The purpose of this research is to examine the history of Pa'beng music ranging from music as an accompaniment to the traditional ceremony of Hodo rituals until now into entertainment music. This research focused on the history of Pa'beng music in the changing times and the change of music function itself. This research uses the qualitative method to describe Pa'beng Music's background as a Hodo ritual accompaniment to produce descriptive data. Descriptive data is in the form of words and actions, therefore requiring methods that allow researchers to capture language and behavior. The data covers interviews, photography, videos, personal documents, and other official recordings.